2013
DOI: 10.1002/ece3.551
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillars selected for large body size and short development time are more susceptible to oxygen‐related stress

Abstract: Recent studies suggest that higher growth rates may be associated with reduced capacities for stress tolerance and increased accumulated damage due to reactive oxygen species. We tested the response of Manduca sexta (Sphingidae) lines selected for large or small body size and short development time to hypoxia (10 kPa) and hyperoxia (25, 33, and 40 kPa); both hypoxia and hyperoxia reduce reproduction and oxygen levels over 33 kPa have been shown to increase oxidative damage in insects. Under normoxic (21 kPa) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
(121 reference statements)
3
22
0
Order By: Relevance
“…As predicted, unnaturally low P O2 (hypoxia) decreases the critical mass (Callier and Nijhout, 2011;. Hypoxia also decreases size at the next moult, final body size and growth rate, and prolongs development (Loudon, 1988;Greenberg and Ar, 1996;Frazier et al, 2001;Henry and Harrison, 2004;VandenBrooks et al, 2012;Harrison et al, 2013;reviewed by Harrison et al, 2006reviewed by Harrison et al, , 2010but Loudon, 1988 showed that hypoxia had no effect on final size). By contrast, the effect of unnaturally high P O2 (hyperoxia) on the critical mass, moulting size and final body size is contradictory (Greenberg and Ar, 1996;Frazier et al, 2001;Henry and Harrison, 2004;Harrison et al, 2010;Callier and Nijhout, 2011;VandenBrooks et al, 2012;.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…As predicted, unnaturally low P O2 (hypoxia) decreases the critical mass (Callier and Nijhout, 2011;. Hypoxia also decreases size at the next moult, final body size and growth rate, and prolongs development (Loudon, 1988;Greenberg and Ar, 1996;Frazier et al, 2001;Henry and Harrison, 2004;VandenBrooks et al, 2012;Harrison et al, 2013;reviewed by Harrison et al, 2006reviewed by Harrison et al, , 2010but Loudon, 1988 showed that hypoxia had no effect on final size). By contrast, the effect of unnaturally high P O2 (hyperoxia) on the critical mass, moulting size and final body size is contradictory (Greenberg and Ar, 1996;Frazier et al, 2001;Henry and Harrison, 2004;Harrison et al, 2010;Callier and Nijhout, 2011;VandenBrooks et al, 2012;.…”
Section: Introductionmentioning
confidence: 70%
“…By contrast, the effect of unnaturally high P O2 (hyperoxia) on the critical mass, moulting size and final body size is contradictory (Greenberg and Ar, 1996;Frazier et al, 2001;Henry and Harrison, 2004;Harrison et al, 2010;Callier and Nijhout, 2011;VandenBrooks et al, 2012;. Furthermore, there are no consistent hyperoxia effects on growth and development rates (Greenberg and Ar, 1996;Frazier et al, 2001;Harrison et al, 2006Harrison et al, , 2013VandenBrooks et al, 2012;. The contradictory results concerning hyperoxia effects may arise either because the ODIM hypothesis is unrealistic or because the applied hyperoxia manipulations have been unrealistically strong.…”
Section: Introductionmentioning
confidence: 99%
“…However, importantly, the so far recognised costs of fast growth are primarily manifested not as costs of integral growth rates but rather as costs of high differential growth rates. The latter included lower starvation resistance (Stoks et al 2006, Scharf et al 2009), oxidative stress (De Block and Stoks 2008, Harrison et al 2013, Smith et al 2016, and higher vulnerability of actively foraging larvae to predators (Gotthard 2000, Stoks et al 2005). An explicit attention to DGR is therefore needed in the optimality analyses of growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Because body size affects reproductive capacity (Davidowitz, ; Honek, ; Kingsolver & Pfennig, ) and development time is related to generation time (Roff, ), both can affect the rate of population increase or the rate of spread of favorable genes. Increase in body size and decrease in development time are the usual result of natural selection acting on individual organisms (Eck, Shaw, Geyer, & Kingsolver, ; Harrison, Cease, VandenBrooks, Albert, & Davidowitz, ; Kingsolver & Huey, ; Kingsolver & Pfennig, ).…”
Section: Introductionmentioning
confidence: 99%
“…size and decrease in development time are the usual result of natural selection acting on individual organisms (Eck, Shaw, Geyer, & Kingsolver, 2015;Harrison, Cease, VandenBrooks, Albert, & Davidowitz, 2013;Kingsolver & Huey, 2008;Kingsolver & Pfennig, 2004).…”
mentioning
confidence: 99%